(untitled) (Journal of Forensic Medicine & Toxicology, 2015)
In spite of being rare, intracranial nail gun injury represents one of the fatal penetrating head injuries. Here we report a case of intracranial nail gun injury in a 28 years old well-trained Bangladeshi construction worker who left the electric nail gun on the edge of the window to pick up one of his tools from the ground. Unfortunately, his leg got entangled in the nail gun cable and thus the nail gun dropped on the ground firing a nail that killed the worker. To the best of our knowledge, this first time death from nail gun injury is reported in the Arab world; although, there are previous reports of survivable nail gun cardiac injuries and cranial injuries from Saudi Arabia. Thus, it is important to raise public awareness about such cases in order to reduce the occurrence of such injuries. Moreover, Health and Safety inspections mandated and supported by law, might be much more effective in reducing nail gun injuries.